Microsavings, Microcredit and Microinsurance: Financial Products of Small Farmer Co-operatives Ltd. in Nepal - Stefan Staschen (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2001)
Rural Finance Nepal (RUFIN) is a joint Nepali-German project, implemented by the Agricultural Development Bank of Nepal (ADBN), with technical assistance from the German Agency for Technical Co-operation (GTZ). RUFIN aims at bringing sustainable financial services to the rural poor. The financial technology employed by any microfinance institution in order to deliver services to its clients is probably the most important factor influencing profitability. Without appropriate loan, savings and insurance products, and the capability to regularly produce innovations, outreach to the poor and ultimately sustainability of microfinance institutions cannot be achieved. This paper addresses these issues by looking into the financial technology employed by selected Small Farmer Co-operatives Ltd. (SFCLs). They are an outgrowth of the Samll Farmer Development Project of ADBN; IFAD was the first major donor of the SFDP. Special emphasis is placed upon the design of savings and loan products, and the savings mobilisation and credit delivery processes of these member-based grassroots organisations. In its analysis, this paper builds upon Working Paper B12, which addressed the issue of financial viability by analysing 33 SFCLs: they managed to increase their financial selfsufficiency ratios from 39% in 1996/97 to 117% in 1999/2000. These insights revealed will allow the reader to better understand how these cooperative microfinance institutions have finally achieved such astonishing performances.
Keywords: 330